Retrospective Study of Pneumony by Aelurostrongylus abstrusus in Cats - Pereira, Paula Reis; Argenta, Fernando Froner; Rolim, Veronica Machado; Oliveira, Eduardo Conceição de; Sonne, Luciana; Pavarini, Saulo Petinatti; Driemeier, David (Acta Scientiae Veterinariae, 2017)
Background: Aelurostrongylus abstrusus is a lungworm of cats with worldwide distribution. The adult forms of this parasite live in terminal bronchioles and alveoli, and can cause an asymptomatic disease or predominantly respiratory clinical signs, which can be occasionally cause of death. The aim of this study is to describe the epidemiological and pathological findings of infection by A. abstrusus through a necropsy retrospective study. Materials, Methods & Results: the necropsy records from the Department of Veterinary Pathology of the Universidade Federal do Rio Grande do Sul were recovered and cats diagnosed with lungworm by Aelurostrongylus abstrusus were selected since January 1998 until December 2015. General data, such as age, sex, breed, clinical signs, and macroscopic lesions, were analyzed and compiled. The histological slides were reviewed by optical microscopy and detailed the microscopic aspects. In this study, were identified 22 cats with varying degrees of lungworm by A. abstrusus, and in 45.5% of the cases, this was the cause of death. Most part of the cats were mixed breed (19/22), and there were no sex predisposition. The age of the cats ranged from four months to 11 years old, and the most frequent age group was three to six years, with nine cases reported. In 37.5% of the cases were reported respiratory clinical signs, such as dyspnea and nasal discharge, and in 62.5%, clinical signs were not specific. The gross findings of the lungs ranged from reddish, or yellowish or white areas, and presence of multiples small, firm, and whitish nodules, measuring more than two centimeters in diameter, with multifocal distribution in the lung surface. Histologically, there was varied amount of parasites in different stages in the alveolar spaces, associated with the inflammatory infiltrate composed of lymphocytes, plasma cells, macrophages, neutrophils and occasional multinucleated giant cells, and hypertrophy and hyperplasia of the pulmonary smooth muscle and the wall of the arteries. Discussion: Aelurostrongylus abstrusus is the principal parasite of lung of cats, with worldwide distribution. In this study, we observed that 40.9% of cases were reported as of 2012, and may be due to a larger propagation of definitive intermediate and paratenic hosts, climate changes and/or the increase of rearing cats, and the consequent increase of hospital routine. Agreeing with the others authors, there is no sex predilection, but differ in the age group, in to the present study, the most frequent age group was between “3 to 6 years” of age (52.9%). The gross findings observed were similar to those described by other authors. Histologically was observed varied amount of parasites, and the degree of inflammatory infiltrate were very similar, but with a slight difference in discrete infiltration (36.4%). Others researchers have identified predominantly severe inflammatory infiltrate (57.9%). Hypertrophy and hyperplasia of pulmonary smooth muscle and the wall of the arteries was moderate (50%), however, in previous studies were severe. The diagnosis of aelurostrongilosis through parasitological tests have proven the occurence this lung parasite in the study region, highlighting the importance of this study by adding epidemiological and pathological data on the disease.